Učestalost upotrebe likovno-umjetničkog djela u nastavi likovne kulture - Brajčić, Marija; Šućur, Mara (2019)
Upoznavanje učenika s likovno-umjetničkom djelom značajan je cilj predmeta likovne kulture. Utjecaj likovno-umjetničkog djela na dječju percepciju, moć uočavanja kao i razvoj estetskih vrijednosti iznimno je važan za daljnji razvoj i napredak učenika ne samo u likovnoj kulturi, već i u ostalim odgojno-obrazovnim područjima. Znanstvena teorija drži da ni jedan nastavni sat likovne kulture ne bi trebao proteći bez prikaza likovno- umjetničkog djela. Cilj istraživanja je bio utvrditi učestalost upotrebe likovno-umjetničkog djela u nastavi likovne kulture u nižim razredima osnovne škole. Uspoređeni su odgovori 80 učitelja s područja Splitsko-dalmatinske županije i 80 studenata četvrte i pete godine Učiteljskog studija u Splitu koji u okviru studija održavaju ispitne satove iz likovne kulture. Svrha je istraživanja bila utvrditi koliko učitelji ili studenti koriste likovna djela na nastavi likovne kulture i na koji način ih predstavljaju učenicima. Istraživanje je pokazalo da većina navedenih varijabli ide u korist studentima, izuzev pitanja koja se odnose na pokazivanja figurativnih djela na nastavi likovne kulture i pokazivanje djela domaćih umjetnika na nastavi likovne kulture, kod kojih ne postoji statistička značajnost. I učitelji u studenti se u podjednakoj mjeri odlučuju za figurativna djela i djela domaćih umjetnika.
Introducing students with the artwork is a significant goal of the subject of visual arts. The influence of the artwork on child perception, the power of observation and the development of aesthetic values is extremely important for the further development and advancement of students not only in visual arts but also in other educational areas. Scientific theory consider that no curriculum lesson of art classes should go without displaying an artwork.The aim of the research was to determine the way of using art works in the teaching of fine arts in the lower grades of elementary school. Compared to 80 teachers from Splitsko – dalmatinska County and 80 students of the fourth and fifth year of the Teacher’s Study in Split, who are conducting test workshops in the field of visual arts. The purpose of the research was to determine to what extent teachers or students use artwork in the teaching of visual arts and how they represent them to the students. The research has shown that most of the variables mentioned are beneficial to students, with the exception of issues related to the display of figurative works in visual art and showing the works of domestic artists in the teaching of visual culture where there is no statistical significance. Teachers and students choose likewise figurative works and works of domestic artists. The research has shown that most of the above variables are beneficial to students, with the exception of issues related to the display of figurative works in the teaching of visual arts and showing the works of domestic artists in the teaching of visual arts, where there is no statistical significance. Teachers and the students chose equally the figurative works and works of domestic artists.
Bibliografske bilješke uz tekst.
Sažetak ; Summary.
Keywords: Likovna kultura -- Likovno djelo -- Nastava likovne kulture -- Osnovnoškolsko obrazovanje